Early Introduction of cART Reverses Brain Aging Pattern in Well-Controlled HIV Infection: A Comparative MR Spectroscopy Study - Boban, Jasmina M.; Kozic, Dusko B.; Brkic, Snezana V.; Lendak, Dajana F.; Thurnher, Majda M. (Frontiers in Aging Neuroscience, 2018)
Introduction: The aim of this study was to compare age-related changes in chronically infected, asymptomatic HIV-positive patients under combination antiretroviral therapy (cART), with age-, gender-, and educational-level-matched healthy subjects, using multi-voxel magnetic-resonance spectroscopy (MRS). Methods: There were 66 chronically infected HIV-positive subjects and 65 age-, gender-, and educational-level-matched control subjects, divided into four groups according to the age: group 1 (20–29 years old), group 2 (30–39), group 3 (40–49) and group 4 (50–59). MRS was performed and ratios of N-acetyl-aspartate (NAA)/creatine (Cr) were analyzed in ten locations of the supracallosal gray matter. For the comparison of NAA/Cr ratios in healthy and HIV-positive subjects, ANCOVA with age and education as covariates was performed. Correlations of NAA/Cr ratios with duration of cART were performed using Pearson’s correlation test. Statistical significance was set at p < 0.05. Results: The NAA/Cr ratios were decreased in the 20–29-year-old HIV-positive subjects in 8/10 locations (p < 0.005) compared to the healthy controls, while in the 50–59-year-old groups they were significiantly lower only in one location (p = 0.004). There were significant positive correlations of NAA/Cr levels with the duration of cART in the oldest group of HIV-positive subjects, while in the youngest group there were no significant correlations. Conclusion: The aging pattern in chronic HIV infection under cART is accentuated rather than accelerated. There is an initial HIV-related neuronal damage with a significant decline in NAA/Cr ratios; after the initiation of cART, however, NAA/Cr ratios increase continuously to become similar to healthy aging individuals, probably due to beneficial effect of long-standing cART. Summary: Brain aging in chronic HIV infection under cART is accentuated, with an initial HIV-related neuronal damage followed by a subtle NAA/Cr increase after the initiation of cART. Under cART, in advanced age, NAA/Cr ratios become similar to healthy aging individuals.